Dihydroartemisinin-Loaded Chitosan Nanoparticles Inhibit the Rifampicin-Resistant Mycobacterium tuberculosis by Disrupting the Cell Wall - Gu, Xiujuan; Cheng, Qi; He, Ping; Zhang, Yan; Jiang, Zhengfang; Zeng, Yali (Frontiers in Microbiology, 2021)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (MTB) is a deadly infection, and increasing resistance worsens an already bad scenario. In this work, a new nanomedicine antibacterial agent, based on dihydroartemisinin (DHA) and chitosan (CS), has been successfully developed to overcome MTB's drug-resistant. To enhance DHA's solubility, we have prepared nanoparticles of DHA loaded CS by an ionic crosslinking method with sodium tripolyphosphate (STPP) as the crosslinking agent. The DHA-CS nanoparticles (DHA-CS NPs) have been fully characterized by scanning electron microscopy, Fourier transforms infrared spectroscopy, dynamic light scattering, and ultraviolet spectrophotometry. DHA-CS NPs show an excellent antibacterial effect on the rifampicin (RFP)-resistant strain (ATCC 35838) and, at a concentration of 8.0 µg/mL, the antibacterial impact reaches up to 61.0 ± 2.13% (n = 3). The results of Gram staining, acid-fast staining, auramine "O" staining and electron microscopy show that the cell wall of RFP-resistant strains is destroyed by DHA-CS NPs (n = 3), and it is further verified by gas chromatography-mass spectrometry. Since all the metabolites identiﬁed in DHA-CS NPs treated RFP-resistant strains indicate an increase in fatty acid synthesis and cell wall repair, it can be concluded that DHA-CS NPs act by disrupting the cell wall. In addition, the resistance of twelve strains is effectively reduced by 8.0 µg/mL DHA-CS NPs combined with RFP, with an effective rate of 66.0%. The obtained results indicate that DHA-CS NPs combined with RFP may have potential use for TB treatment.